Effect of Metal Ions on the Hydrolysis of the Schiff Bases Derived from 5-Chloro-4,6-Dimethyl-2-Hydroxy Benzaldehyde. - D. BHOSALE, VIDHYA; SANDHYA,; SHETYE, S.; C. VICHARE, KRISHNAKANT (Asian Journal of Chemistry, 2010)
The catalytic effect of Ni(lI), Ce(Ill) and Zr(IV) ions on the hydrolysis of substituted derivatives of 5-chloro-4,6-dimethyl-2-hydroxy benzaldehyde has been studied spectrophotometrically at 298 ± 1 K. The rate of hydrolysis by the different metal ions follows the sequence Zr(IV) > Ni(II) > Ce(III) which is higher than the rate of hydrolysis in the absence of metal ions. A suitable reaction mechanism has been suggested for the metal ion catalyzed hydrolysis of the imines under study.